Ochrona środowiska przyrodniczego w pracach prof. Stefana Kozłowskiego - Michał Latawiec (Studia Ecologiae et Bioethicae)
The aim of this article is to introduce selected issues raised by Prof. Stefan Kozlowski, for the benefit of environmental protection. During fifty years of his professional activity, many important, memorable issues have appeared. The article points at Kozlowski’s attempt to outline problems concerning nature conservation, which, in spite of beautiful tradition, was perverted by the political system of that time. This leads to many cases of abuse in natural resources management and excessive exploitation of those resources. Another important question is Kozlowski’s striving to establish area forms of nature conservation. Realizing these aims, he brings to formulate a full legal system of all-natural components protection. The last subject, that is mentioned in the article, is Kozlowski’s contribution to the implementation of sustainable development rules. Such development should be a superior rule in environmental policy leading by state. Kozlowski often advances courageous thesis, that was constructed in the taste of constructive criticism. Proposed solutions often have system features.